8 1/2 [videorecording (DVD)] - Fellini, Federico; Mastroianni, Marcello, 1924-1996; Cardinale, Claudia, 1939-; Rota, Nino, 1911-1979 (Criterion collection, 2001)
A semi-autobiographical film of Fellini about a film director (Mastroianni) who finds himself creatively barren at the peak of his career. He fantasizes at a resort to get away from the pressures of wife and staff.